Efeito da ingestão dos óleos de soja e de peixe na alergia alimentar induzida experimentalmente em camundongos - Olivia Goncalves de Matos (2010)
The incidence of allergic disease is increasing in both children and adults. It is well accepted that an imbalance in the consumption of oil rich in long-chain omega 3 polyunsaturated fatty acids (n-3PUFA) and long-chain omega 6 polyunsaturated fatty acids (n-6PUFA) can modulate the immune function, increasing the risk of allergic reactions. We investigated in this study the protective effect of fish oil (rich in n-3PUFA) in a experimental model of food allergy induced in mice sensitized by ovalbumin (OVA). In order to evaluate the progress of the allergy, we assessed the weight loss over the time, serum levels of IgE and IgG1, eosinophil infiltration, intestinal mucus production by goblet cells and leukocyte recruitment in the GI microvasculature. Mice were sensitized with OVA and challenged orally by adding OVA to the chow (PROTOCOL 1) or by substituting the water source to an egg whitesolution (20%; PROTOCOL 2). In both protocols the lipid source in the chow was composed by soybean oil (chow 1 control), fish oil (chow 2) or a mixture of the two oils (chow 3). The ingestion of a fish oil loaded chow or a mixture of two oils led to reduced levels of serum IgE and IgG, eosinophil infiltration, intestinal mucus production and reduced rolling cells in the GI microvasculature, in comparison to controls (soybean oil as lipid source). These results were found only in PROTOCOL1, showing that the benefic effects depend of the antigen vehicle. Taken together, these data suggest that the regular consumption of fish oil may reduce several classic signals of food allergy.